Hubungan Dukungan Kepala Keluarga Dengan Kualitas Hidup Klien Diabetes Militus Tipe II Di Wilayah Kerja Puskesmas Batunadua Kecamatan Padangsidimpuan - Parinduri, Julidia Safitri; ., Anita Ria; ., Siti Asma (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Diabetes mellitus is a metabolic disorder that is genetically and clinically heterogeneous manifestations including in the form of loss of carbohydrate tolerance. The purpose of this study was to determine the relationship Support the Head of Family Life Quality Client Type II Diabetes Mellitus. This research was conducted in the sub-district Puskesmas Batunadua Padangsidimpuan. by using descriptive correlation. The number of samples examined as many as 30 people using total sampling. The collection of data by using a questionnaire. From the analysis of the data found that the Support Households in 30 respondents showed respondents support the family heads of both categories with quality of life for as many as 11 people (36.66%), unfavorable category as many as 19 people (63.34%), found that based on the results of Spearman obtained p-value 0.00 (<0.05) so that Ho refused and Ha accepted, meaning there is a relationship with the families, Head of Support Life Quality Client type II Diabetes Mellitus. Suggested to health centers and health agencies that exist in the location in order to further improve mutuh research and education on public health, especially to the head of the family who have family members with diabetes mellitus type II in the sub-district Puskesmas Batunadua Padangsidimpuan.